Liberalism, Marxism and the struggle for the state : prolegomena to the study of public administration - Bates, Richard J., 1941-; Deakin University. School of Education. Open Campus Program (Waurn Ponds, Vic. : Deakin University : Distributed by Deakin University Press, 1985)
Produced for unit ESA844 (Administrative context of schooling) offered by the School of Education in Deakin University's Open Campus Program.
Bibliography: p. 145-150.
For tertiary students.
Keywords: Political ideologies: Liberalism; Liberalism